Design the model control of wind turbine speed by bevel-gear system - Nguyễn Ngọc Phương; Nguyễn Duy Phương (Journal of Technical Education Science, 2013)
Today, the researches of wind turbine is how to effectively control the speed of the turbine when the wind speed changes, ensure that the turbines are highest effective performance. The paper content presented a system control of wind turbine speed by using the bevel-gear system to revolve the turbine blade, with method design, calculation and manufacturing absolutely no complex. Experimental model was conducted with different spindle speeds and noted the ability to control the speed of the speed system.The fist results show that the research process has brought success in control the wind turbine speed, the turbine are highest effective performance ensure stability and balance for the whole turbine system during operation.